Electrodeposition and growth mechanism of preferentially orientated nanotwinned Cu on silicon wafer substrate. Issue 10 (October 2018) - Sun, Fu-Long; Gao, Li-Yin; Liu, Zhi-Quan; Zhang, Hao; Sugahara, Tohru; Nagao, Shijo; Suganuma, Katsuaki
Abstract: Homogeneous columnar Cu film with fully embedded nanotwins was successfully fabricated on Ti/Cu seed layer on silicon wafer. The nanotwins with thickness of tens of nanometers are generally parallel to the silicon surface, showing a strong (111) preferred orientation. The acid concentration was found to be important in influencing the formation of nanoscale twins. By adjusting the acid concentration, the nanotwins can be induced from the top columnar grain to middle columnar grain and reach the bottom equiaxed grain, and a microstructural transformation model was given. A theory focusing on the cathode overpotential was proposed to reveal the effect of acid concentration on the growth mechanism of nanoscale twins. An appropriate adsorption proportion of hydrogen on cathode (acid concentration 17 ml L −1 ) could increase the overpotential which supplies adequate nucleation energy for nanoscale twins formation.